ISM AL- MA’RIFAH (NOMINA DEFINIT) BERKASUS GENETIF DALAM KITAB KHULASHOH NURUL YAQIN JUZ 2 KARYA UMAR ABDUL JABBAR (ANALISIS SINTAKSIS) - Aji, Dimas Kurnia; Nawawi, Muchlisin; Miftahuddin, Ahmad (Lisanul Arab: Journal of Arabic Learning and Teaching, 2021)
The discussion of nahcw science is very large, one of which is about Ism Al- Ma’rifah (Definite Noun) Genitive Case. The researcher chose the book Khulashoh Nurul Yaqin chapter 2 since there are many kinds of ism al- ma’rifah genitive case so that they can be analyzed to improve the readers‟ understanding of this book and is expected to be useful for increasing knowledge development. This is a qualitative study with library research design. Data in the form of ism al ma’rifah (definite noun) genitive case are sourced from the book Khulashoh Nurul Yaqin chapter 2. The instrument used in this study was a data card. The data collection technique used the documentation method. The data analysis technique used the distributional method. The result of this study showed that there are about 430 data on ism al- ma’rifah (definite noun) genitive case found in the book Khulasoh Nurul Yaqin chapter 2. The researcher took 100 data samples with purposive sampling technique (1) type ism al- ma’rifah (definite noun) genitive case consisting of 26 data types ism ‘alam, 15 data types ism dhamir, 1 data types ism isyarah, 1 data types ism maushul, 41 data types ism al-mu’arraf bi al, 16 data types ism al-mudhafu ilal ma’rifah. (2) Functions of ism al- ma’rifah (definite noun) genitive case consist of 43 data as majrur which changes into jarr with harf jar, 41 data as majrur which changes into jarr with idhafah, 16 data that function as majrur which changes into jarr with attawabi’ (9 data as na’at and 7 data as athaf (ma’thuf)).